15 Years Cemeti Art House : Exploring Vacuum : 1988-2003. - Situmorang, Saut; Kent, Elly; Cemeti Art House, Yogyakarta; Jaarsma, Mella; Adipurnomo, Nindityo (Yogyakarta : Cemeti Art House, 2003)
Jaarsma, Mella ; Fadjri, Raihul ; Irianto, Asmudjo Jono ; Anusapati ; Burhan, Agus ; Halim HD ; Kurniawan, Agung ; Wahyudi, Popok Tri ; Susanto, Mikke ; Maryanto, M. Dwi ; Wiyanto, Hendro ; Wardani, Farah P. ; Hong Djien, Oei ; Rath, Amanda K. ; Gaweewong, Gridthiya Jeab ; Hanru, Hou ; Clark, Christine ; Prawoto, Eko Agus ; Zaelani, Rizki A. ; Ushiroshoji, Masahiro ; Budiman, Kris ; Siregar, Aminudin Th. ; Nugroho, Eko ; Hasan, Asikin ; Mohamad, Goenawan ; Juliastuti, Nuraini ; Sumartono ; Situmorang, Saut ; Willems, Gerrit ; Adipurnomo, Nindityo ; Moelyono ; Ariestyowanti, Santi ; Volunteero, Yustoni ; AG. Kus Widananto (Jompet) ; Alfi, Jumaldi ; Ratnawulan, Syagini ; Darmawan, Ade ; Arahmaiani ; Murti, Krisna ; Witjaksono, Bambang Toko ; Pius, Sigit ; Sanjaya, Tisna ; Indratma, Samuel ; Harsono, F.X. ; Soerjoatmodjo, Yudhi Irawan
boek